Enhancing CAR-T Efficacy: The Role of Anti PD-1/PD-L1 Checkpoint Inhibitors in Modern Cancer Treatment - Rishi Kant; Prashanjit Roy; Amandeep Kaur; Ranjeet Kumar (Journal of Coloproctology, 2025)
The article "Enhancing CAR-T Efficacy: The Role of Anti PD-1/PD-L1 Checkpoint Inhibitors in Modern Cancer Treatment" provides an exhaustive study on CAR-T cell therapy and its role in cancer treatment, focusing on the problem of T-cell exhaustion and tumor immune evasion. Anti-PD-1/PD-L1 checkpoint inhibitors are said to help achieve enhanced CAR-T therapy by countering immune suppression within the tumor microenvironment. The introduction emphasizes the success level of CAR-T cells, especially in B-cell hematologic malignancies, while humbly candid in its limitation concerning solid tumors through mechanisms of immunosuppression. Of specific interest herein are the PD-1 and PD-L1 pathways as key immune checkpoints exploited by cancer to escape an immune response. To elaborate on this, it also explains how tumors upregulate PD-L1 to prevent T-cell functions through T-cell exhaustion, which entails depression in cytokine production and proliferation. The article explains the mechanisms of T-cell exhaustion: chronic antigen exposure, transcriptional reprogramming, metabolic dysfunction, and the suppressive nature of the tumor microenvironment. All these mechanisms combined lead to a loss of T-cell efficacy in counteracting tumor progression. The PD-1/PD-L1 axis preserves T-cell exhaustion and inhibits a strong immune response against the tumor. The paper puts forth the argument that the combination of CAR-T cell therapy with PD-1/PD-L1 checkpoint inhibitors leads to the reversal of immune suppression, improving T-cell function and persistence. A review of the preclinical and clinical trials, especially for solid tumor malignancies, puts forth advantages as well as challenges. Such challenges are experienced in terms of T-cell exhaustion, immunosuppressive tumor microenvironments, optimization of a dose, issues of toxicity, and inconsistent clinical outcomes.